2018
DOI: 10.31235/osf.io/suqnk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Growth of US Top Income Inequality: A Hierarchical Redistribution Hypothesis

Abstract: What accounts for the growth of US top income inequality? This paper proposes a hierarchical redistribution hypothesis. The idea is that US firms have systematically redistributed income to the top of the corporate hierarchy. I test this hypothesis using a large-scale hierarchy model of the US private sector. My method is to vary the rate that income scales with hierarchical rank within modeled firms. I find that this model is able to reproduce four intercorrelated US trends: (1) the growth of the top 1% incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Possibly. I have previously found that the growth of top US incomes may be due to a redistribution of income towards the tops of firm hierarchies [65].…”
Section: Open Questionsmentioning
confidence: 99%
“…Possibly. I have previously found that the growth of top US incomes may be due to a redistribution of income towards the tops of firm hierarchies [65].…”
Section: Open Questionsmentioning
confidence: 99%
“…This changing income distribution within US firms, and the resulting fall in wage shares and weak effective demand and investment rates, has been associated with increasingly hierarchical structures and the systematic redistribution of income to the top of the corporate hierarchy (Fix, ). This is reflected in a swelling CEO pay ratio: Disney, while cutting its workers’ real pay by 15 per cent, gave its CEO a compensation package equal to the pay of over 9,000 Disneyland workers .…”
Section: The Distribution Of ‘Market’ Income Across the World: ‘Markementioning
confidence: 99%
“…Possibly. Fix (2018a) finds that the growth of top US incomes may be due to a redistribution of income towards the tops of firm hierarchies.…”
Section: Open Questionsmentioning
confidence: 99%